Expression and activity of alcohol and aldehyde dehydrogenases in melanoma cells and in melanocytes - Amann, Philipp M.; Freudenberger, Muriel; Holland-Cunz, Stefan; Eichmüller, Stefan B.; Bazhin, Alexandr V. (Journal of cellular biochemistry, 2012)
Disturbances in vitamin A metabolism are an important attribute of some cancer cells. Most evidence point that these disturbances lead to decreasing of the retinoic acid concentration in tumor cells. Up to now, in benign and malignant skin cells the features of vitamin A metabolism with its participating enzymes are not entirely understood. Alcohol and aldehyde dehydrogenases (ALDH) are involved in the retinol metabolism, oxidizing retinol, and retinal in retinoic acid or reducing retinal in retinol. In this work we investigated the expression and enzymatic activity of alcohol and ALDH in melanoma cells compared to their benign counterparts. We demonstrated that melanoma cell lines and melanocytes despite similar pattern of the enzyme expression, show different general ALDH activity. Retinal, the substrate of ALDH, could stimulate the ALDH activity through up-regulation of retinaldehyde dehydrogenase 1 and aldehyde dehydrogenase 6. Furthermore, we found that retinoids regulate alcohol dehydrogenase activity, probably via effects on alcohol dehydrogenase expression at the post-transcriptional level. We suggest that melanoma cells in contrast to melanocytes should favor the retinal reduction over its oxidation. The decreasing cellular amount of the precursor molecules of retinoic acid could result in a changed gene regulation in melanoma cells.
First published: 20 October 2011
Gesehen am 17.05.2018